1987
DOI: 10.1128/aem.53.4.665-671.1987
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of plasmid pHSV106 from Escherichia coli HB101 in a laboratory-scale waste treatment facility

Abstract: The mobilization of plasmid pHSV106 from Escherichia coli HB101, in a laboratory model waste treatment facility, by both laboratory and indigenous wastewater strains of E. coli was monitored by transfer of antibiotic resistance characteristics and by detection of pHSV106 DNA sequences in recipient celis. The mobilization was demonstrated to occur under several different treatment conditions, such as different media composition, microbial concentrations, and waste flow rates. The herpes simplex virus thymidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…Wastewater treatment plants (WWTP) are of particular significance as interfaces between different environmental compartments, such as hospitals and surface waters, and therefore may facilitate gene spread between these habitats. Biofilm and flock formation, high bacterial densities and metabolic activities in the aerator and clarifiers allow -and may even promote -genetic exchange by conjugation in these treatment facilities (Mach & Grimes, 1982;Mancini et al, 1987). Over the past 20 years several studies have provided evidence that WWTP serve as important reservoirs for MGE encoding drug resistance (McPherson & Gealt, 1986;Mancini et al, 1987;Gealt, 1988;Fujita et al, 1993;Bauda et al, 1995;Dröge et al, 2000;Heuer et al, 2002;Smalla & Sobecky, 2002;Tennstedt et al, 2003Tennstedt et al, , 2005Szczepanowski et al, 2004a;Szczepanowski et al, 2005;Bönemann et al, 2006).…”
Section: Introduction: Impact Of Wastewater Treatment Plants On the Hmentioning
confidence: 99%
“…Wastewater treatment plants (WWTP) are of particular significance as interfaces between different environmental compartments, such as hospitals and surface waters, and therefore may facilitate gene spread between these habitats. Biofilm and flock formation, high bacterial densities and metabolic activities in the aerator and clarifiers allow -and may even promote -genetic exchange by conjugation in these treatment facilities (Mach & Grimes, 1982;Mancini et al, 1987). Over the past 20 years several studies have provided evidence that WWTP serve as important reservoirs for MGE encoding drug resistance (McPherson & Gealt, 1986;Mancini et al, 1987;Gealt, 1988;Fujita et al, 1993;Bauda et al, 1995;Dröge et al, 2000;Heuer et al, 2002;Smalla & Sobecky, 2002;Tennstedt et al, 2003Tennstedt et al, , 2005Szczepanowski et al, 2004a;Szczepanowski et al, 2005;Bönemann et al, 2006).…”
Section: Introduction: Impact Of Wastewater Treatment Plants On the Hmentioning
confidence: 99%
“…xenobiotic degrading GEMS). To date, researchers studying gene transfer in sewage works have either concentrated on in vitro studies using raw wastewater-isolated strains [2,3], or investigated the settlement tanks of primary sewage treatment with the aid of membrane diffusion chambers [4,5], or made use of model activated sludge units (ASU, a major secondary treatment process [6]) in their studies [7,8]. However, no one has yet investigated gene transfer in percolating filter beds (the other major secondary treatment process [6]), hence the reason for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Fax: (33) 68 88 16 99. recombinant DNA to the indigenous microbial populations are better understood [2][3][4]. The use of nonconjugative plasmids may limit interbacterial transfer, but such plasmids may be mobilized by self-transmissible plasmids via conjugative mobilization or cointegration [4][5][6]. Previous studies have reported that bacterial strains from wastewater, river and seawater can mobilize nonconjugative plasmids in microcosms [4,7].…”
Section: Introductionmentioning
confidence: 99%